A high temperature resistant ceramic fiberboard and preparation method thereof
Through in-situ cross-linking and polymerization of acrylamide monomers and silica sol binders, the problem of the adhesive floating in the drying process of ceramic fiberboard is solved, the heat resistance and strength of ceramic fiberboard are improved, and more uniform Component distribution and density are improved.
Patent Information
- Application Number
- CN202410752272.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-12
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-06-12
AI Technical Summary
Wet molding to prepare ceramic fiberboard is floating during drying, affecting its heat resistance and strength.
In situ cross-polymerization of acrylamide monomers and silica sol binder is used to flocculate the polymerization reaction to form a cross-linked polymer to inhibit the floating of the binder and improve the heat resistance and strength of the ceramic fiberboard.
It effectively improves the heat resistance and strength of ceramic fiberboard, prevents the adhesive from floating during the drying process, and improves the density and component distribution uniformity of ceramic fiberboard.
Smart Images

Figure BDA0004888385140000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ceramic fiberboards, and in particular to a high temperature resistant ceramic fiberboard and a preparation method thereof. Background Art
[0002] Ceramic fiberboard is an excellent lightweight refractory material with the advantages of low density, high temperature resistance, low thermal conductivity, small heat capacity, low heat storage, good thermal insulation, good thermal shock resistance, stable chemical properties, and non-toxicity. In comparison, traditional refractory ceramics or refractory bricks are mostly sintered from powder or particles, with high product density, poor thermal shock resistance, and difficult to mechanically cut and process. Therefore, in some high-temperature equipment, the use of fiberboard to replace refractory bricks can play a role in energy saving and efficiency improvement, and because the density of fiberboard is small, it is easier to achieve lightweight and large-scale equipment. Ceramic fiberboard also has high strength, so it is suitable for high-temperature fields that require rigid strength of products. Fiberboard has high compressive strength, long service life, low thermal conductivity, good toughness, precise size, good flatness, easy cutting and installation, convenient construction, and excellent wind erosion resistance and sound absorption and noise reduction performance. Due to these excellent physical and chemical properties, fiberboard occupies an important position in the steel industry, non-ferrous metal industry, glass industry, light industry and other fields.
[0003] At present, there are three main production processes for ceramic fiberboard: wet molding, dry molding and colloid molding. Among them, the ceramic fiberboard prepared by wet molding has a higher density and greater hardness, so it is often used to prepare refractory insulation materials. Its main process is to cut the ceramic fiber raw material into pieces and mix it with a binder to obtain a slurry, and then vacuum mold it in a water-washed mold.
[0004] At present, there are many technologies for preparing ceramic fiberboards by wet forming. For example, patent CN116553941A discloses a high temperature resistant ceramic fiberboard and its preparation method; the preparation method comprises the following steps: a) chopping alumina fibers, mixing with pure water and wet strength agent, dispersing, then adding alumina powder and silica sol, stirring evenly, to obtain a mixture; b) pouring starch aqueous solution into the mixture obtained in step a) for flocculation, to obtain slurry; c) wet vacuum forming the slurry obtained in step b), and drying to obtain a high temperature resistant ceramic fiberboard. The preparation method provided by the invention selects specific raw materials and specific process steps to achieve better overall interaction. The prepared high temperature resistant ceramic fiberboard can be used at high temperatures of 1600°C and above and has excellent properties of high strength and high temperature creep resistance, and has extremely low expansion and contraction at high temperatures.
[0005] However, the inventors have discovered that the problem with using a wet forming process to prepare ceramic fiberboards is that, whether the wet blank is directly dried to obtain a ceramic fiberboard or further sintered to prepare a ceramic fiberboard, the wet blank needs to be dried. However, during this process, as the water evaporates, the original binder in the wet blank will float up, which will, on the one hand, result in excessive binder on the surface, affecting its heat resistance, and on the other hand, will also affect the overall strength of the ceramic fiberboard.
[0006] Therefore, it is necessary to provide a high temperature resistant ceramic fiberboard with good heat resistance and strength. Summary of the invention
[0007] The present application provides a high temperature resistant ceramic fiberboard and a preparation method thereof. The high temperature resistant ceramic fiberboard has good heat resistance and strength.
[0008] In a first aspect, the present application provides a method for preparing a high temperature resistant ceramic fiberboard, comprising the following steps:
[0009] S10: dispersing the refractory ceramic fiber, the refractory ceramic filler and the silica sol binder in water to obtain a mixed solution;
[0010] S20: adding acrylamide monomers and a cross-linking agent to the mixed solution, initiating polymerization reaction and flocculation to obtain a slurry;
[0011] S30: wet vacuum forming the slurry, and drying it to obtain a high temperature resistant ceramic fiberboard.
[0012] According to the present application, by using acrylamide monomers for in-situ cross-linking polymerization and cooperating with silica sol binder, refractory ceramic fibers and refractory ceramic fillers can be quickly flocculated and settled. In the subsequent drying process, the cross-linked acrylamide polymers and silica sol binder are not easy to float, thereby effectively improving the heat resistance and strength of high-temperature resistant ceramic plates.
[0013] In some embodiments, the refractory ceramic fiber includes at least one of polycrystalline mullite fiber, zirconia fiber, and magnesium aluminum spinel fiber; and the length of the refractory ceramic fiber is 0.1 to 10 mm.
[0014] In some embodiments, the refractory ceramic filler includes at least one of polycrystalline mullite particles, zirconia particles, and magnesia-alumina spinel particles; and the average particle size of the refractory ceramic filler is 5 to 200 nm.
[0015] In some embodiments, step S10 specifically includes: dispersing 10 parts by mass of refractory ceramic fibers, 15-40 parts by mass of refractory ceramic fillers and 5-20 parts by mass of a silica sol binder having a solid content of 20wt%-40wt% in 300-500 parts by mass of water to obtain a mixed solution.
[0016] In some embodiments, the acrylamide monomer includes at least one of acrylamide and methacrylic acid amide.
[0017] In some embodiments, the cross-linking agent includes N,N'-methylenebisacrylamide and modified graphene oxide, and the modified graphene oxide is obtained by modifying graphene oxide with an unsaturated silane coupling agent and a fluorine-containing silane coupling agent.
[0018] In some embodiments, the modified graphene oxide is prepared by the following method:
[0019] 10 parts by mass of graphene oxide are dispersed in 200-500 parts by mass of ethanol, and then ultrasonically dispersed. Then, 5-10 parts by mass of vinyltrimethoxysilane and 1-5 parts by mass of (3,3,3-trifluoropropyl)methyldimethoxysilane are added, and the mixture is heated for reaction to obtain modified graphene oxide.
[0020] In some embodiments, the mass ratio of the refractory ceramic fiber to the acrylamide monomer is 1:0.1-0.2; the mass ratio of the acrylamide monomer to the cross-linking agent is 1:0.01-0.2.
[0021] In some embodiments, in step S30, the wet vacuum forming specifically includes: using a vacuum degree of 0.03-0.06 MPa for suction filtration, and using a roller to press, and the roller pressing pressure is 0.05-0.1 MPa.
[0022] In a second aspect, the present application provides a high temperature resistant ceramic fiberboard, which is prepared according to the method described in any embodiment of the first aspect. DETAILED DESCRIPTION
[0023] The various embodiments or implementation schemes in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments.
[0024] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the implementation or examples are included in at least one implementation or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more implementations or examples in a suitable manner.
[0025] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0026] As described in the background technology above, wet forming to prepare ceramic fiberboard has the advantage of high density, and high density can effectively improve the heat resistance and strength of the ceramic fiberboard, so wet forming is generally used to prepare high temperature resistant ceramic fiberboard.
[0027] The inventors found that the problem of preparing high temperature resistant ceramic fiberboard by wet molding is that during the drying process of the wet blank, as the water evaporates, the binder will float up, which significantly affects the overall heat resistance and strength of the ceramic fiberboard. However, no effective solution to improve the above problem has been proposed in the current related art.
[0028] Based on this, the present application provides a high temperature resistant ceramic fiberboard and a preparation method thereof, which can effectively suppress the floating of the binder during the drying process of the wet blank by using a specific process, thereby effectively improving the heat resistance and strength of the high temperature resistant ceramic fiberboard. The specific implementation methods of the present application are described in detail below.
[0029] In a first aspect, the present application provides a method for preparing a high temperature resistant ceramic fiberboard, comprising the following steps:
[0030] S10: dispersing the refractory ceramic fiber, the refractory ceramic filler and the silica sol binder in water to obtain a mixed solution;
[0031] S20: adding acrylamide monomers and a cross-linking agent to the mixed solution, initiating a polymerization reaction and flocculating to obtain a slurry;
[0032] S30: wet vacuum forming the slurry, and drying it to obtain a high temperature resistant ceramic fiberboard.
[0033] According to the present application, by using acrylamide monomers for in-situ cross-linking polymerization and cooperating with silica sol binder, refractory ceramic fibers and refractory ceramic fillers can be quickly flocculated and settled. In the subsequent drying process, the cross-linked acrylamide polymers and silica sol binder are not easy to float, thereby effectively improving the heat resistance and strength of high-temperature resistant ceramic plates.
[0034] Specifically, in step S10, refractory ceramic fibers and refractory ceramic fillers are used as the main materials of the high temperature resistant ceramic fiberboard. Since the main heat resistance of the high temperature resistant ceramic fiberboard is related to the ceramic fiber raw material, the refractory ceramic fibers and refractory ceramic fillers can ensure that it has good heat resistance. The combination of ceramic fibers and ceramic fillers is conducive to further improving the density of the ceramic fiberboard, thereby further improving the heat resistance and strength of the ceramic fiberboard. The silica sol binder is used as the inorganic binder, in which the silica gel particles are negatively charged, which is conducive to the subsequent flocculation and sedimentation of the main material with the acrylic amine cross-linked polymer. At the same time, it can be sintered at high temperature, which can improve the heat resistance and strength of the ceramic fiberboard.
[0035] In step S20, acrylamide monomers and cross-linking agents are added to a mixed solution of ceramic fibers, ceramic fillers and silica sol binders to perform an in-situ cross-linking reaction. At the same time, due to the presence of amide bonds in acrylamide, the monomers and their cross-linked polymers are positively charged. As cross-linking proceeds, under the action of acrylamide cross-linked polymers and silica sol, refractory ceramic fibers and refractory ceramic fillers will flocculate and settle. In this process, sedimentation and cross-linking polymerization occur simultaneously, which can promote the uniform distribution of the main material and the silica sol binder and acrylamide cross-linked polymer, thereby facilitating the suppression of the floating of the silica sol binder and the acrylamide cross-linked polymer of the wet blank during the subsequent drying process, and improving the uniformity of the distribution of the components in the ceramic fiberboard, thereby effectively improving the heat resistance and strength of the ceramic fiberboard.
[0036] In step S30, wet vacuum forming is used, which is beneficial to improving the density of the wet blank after forming, thereby improving the density of the high temperature resistant ceramic fiberboard, so that the high temperature resistant ceramic fiberboard has good heat resistance and strength.
[0037] It can be understood that by using acrylamide monomers for in-situ crosslinking, the flocculation and sedimentation rate is slower than that of directly adding acrylamide polymers, and it is easier to disperse evenly on the surface of refractory ceramic fibers and refractory ceramic fillers. At the same time, under the electrostatic adsorption effect of acrylamide monomers and silica sol, the distribution of the components of the wet blank is more uniform, and the acrylamide cross-linked polymer formed by in-situ crosslinking has a larger steric hindrance, which can make the binder in the wet blank less likely to float, and then the uniformity of the distribution of the components in the ceramic fiberboard is improved, thereby effectively improving the heat resistance and strength of the ceramic fiberboard.
[0038] In some embodiments, the refractory ceramic fiber includes at least one of polycrystalline mullite fiber, zirconia fiber, and magnesium aluminum spinel fiber; and the length of the refractory ceramic fiber is 0.1 to 10 mm.
[0039] In some of the above embodiments, a refractory ceramic fiber with good heat resistance is exemplified, and the use of the above fiber can make the ceramic fiber board have good heat resistance. At the same time, it can be understood that the refractory ceramic fibers include but are not limited to the above, and those skilled in the art can select other refractory ceramic fibers according to actual needs. At the same time, the length of the refractory ceramic fiber is limited to 0.1 to 10 mm. Shorter ceramic fibers are conducive to further improving the density of the ceramic fiber board, thereby further improving the heat resistance and strength of the ceramic fiber board.
[0040] In some embodiments, the refractory ceramic filler includes at least one of polycrystalline mullite particles, zirconia particles, and magnesia-alumina spinel particles; and the average particle size of the refractory ceramic filler is 5 to 200 nm.
[0041] In some of the above embodiments, a refractory ceramic filler with good heat resistance is exemplified, and the use of the above filler can make the ceramic fiberboard have good heat resistance. At the same time, it can be understood that the refractory ceramic filler includes but is not limited to the above-mentioned ones, and those skilled in the art can choose other refractory ceramic fillers according to actual needs. At the same time, the average particle size of the refractory ceramic filler is limited to 5 to 200 nm, and the ceramic filler with a smaller particle size is conducive to further improving the density of the ceramic fiberboard, thereby further improving the heat resistance and strength of the ceramic fiberboard.
[0042] In some embodiments, step S10 specifically includes: dispersing 10 parts by mass of refractory ceramic fibers, 15-40 parts by mass of refractory ceramic fillers and 5-20 parts by mass of a silica sol binder having a solid content of 20wt%-40wt% in 300-500 parts by mass of water to obtain a mixed solution.
[0043] In some of the above embodiments, the mass fraction of each raw material is specifically defined, and the ceramic fiberboard obtained under this condition has better heat resistance and strength. It can be understood that the silica sol binder is a silica sol dispersed in water. As an example, the silica sol binder used in this application is a silica sol with a solid content of 30wt% and a particle size of 10 to 15nm.
[0044] In some embodiments, the acrylamide monomer includes at least one of acrylamide and methacrylic acid amide. The above acrylamide monomers have good water solubility and are more likely to undergo cross-linking polymerization in the slurry, thereby promoting the sedimentation of fibers and fillers, having better bonding properties, and further improving the heat resistance and strength of the ceramic fiberboard.
[0045] In some embodiments, the crosslinking agent includes N,N'-methylenebisacrylamide and modified graphene oxide, and the modified graphene oxide is obtained by modifying graphene oxide with an unsaturated silane coupling agent and a fluorine-containing silane coupling agent.
[0046] In some of the above embodiments, the crosslinking agent includes N,N'-methylenebisacrylamide and modified graphene oxide, wherein the role of N,N'-methylenebisacrylamide is mainly to increase the crosslinking sites of the polymer, thereby increasing the crosslinking degree of the polymer, wherein the modified graphene oxide is obtained by modifying graphene oxide with an unsaturated silane coupling agent and a fluorine-containing silane coupling agent, so that unsaturated bonds and fluorine-containing segments are grafted on the modified graphene oxide, wherein the unsaturated bonds can react with acrylamide monomers and graft with crosslinked polymers. Since the modified graphene oxide is a two-dimensional structure with The larger specific surface area results in a greater steric hindrance in the overall slurry system, making it less likely for the cross-linked polymer to float during the subsequent drying process. In addition, since the cross-linked polymer and the colloid particles in the silica sol are mainly combined through electrostatic action, as the drying proceeds, the electrostatic action weakens, causing the smaller silica particles in the silica sol to float. Since the fluorine atoms in the fluorinated segments on the modified graphene oxide have a strong force with silica, the interaction between the binders is enhanced, which can further limit the floating of the binder, thereby further improving the heat resistance and strength of the ceramic fiberboard.
[0047] It should be noted that the unsaturated silane coupling agent and the fluorine-containing silane coupling agent have well-known meanings in the art. The unsaturated silane coupling agent is a silane coupling agent containing an unsaturated carbon-carbon bond. As an example, the unsaturated silane coupling agent may be vinyltrimethoxysilane; the fluorine-containing silane coupling agent is a silane coupling agent containing fluorine atoms. As an example, the fluorine-containing silane coupling agent may be (3,3,3-trifluoropropyl)methyldimethoxysilane.
[0048] In some embodiments, the crosslinking agent is a mixture of N,N'-methylenebisacrylamide and modified graphene oxide in a mass ratio of 1:3 to 6. In this case, the ceramic fiberboard has better heat resistance and strength.
[0049] In some embodiments, the modified graphene oxide is prepared by the following method:
[0050] 10 parts by mass of graphene oxide are dispersed in 200-500 parts by mass of ethanol, and then ultrasonically dispersed. Then, 5-10 parts by mass of vinyltrimethoxysilane and 1-5 parts by mass of (3,3,3-trifluoropropyl)methyldimethoxysilane are added, and the mixture is heated for reaction to obtain modified graphene oxide.
[0051] In some of the above embodiments, the modified graphene oxide obtained at this time serves as a cross-linking agent, which can further limit the floating of the binder during the drying process of the wet blank, so that the ceramic fiberboard has better heat resistance and strength.
[0052] In some embodiments, the mass ratio of refractory ceramic fiber to acrylamide monomer is 1:0.1-0.2; the mass ratio of acrylamide monomer to crosslinking agent is 1:0.01-0.2. At this time, the crosslinked polymer obtained by crosslinking polymerization can effectively bond the main material, and the binder is less likely to float during the drying process of the obtained wet blank, thereby further improving the heat resistance and strength of the ceramic fiberboard.
[0053] In some embodiments, flocculation by initiating polymerization reaction specifically includes: adding an initiator, causing polymerization reaction flocculation at 50-70° C. for 3-8 hours, and the mass ratio of acrylamide monomer to crosslinking agent is 1:0.01-0.05. The initiator includes but is not limited to ammonium persulfate, potassium persulfate, etc.
[0054] In some embodiments, in step S30, wet vacuum forming specifically includes: using a vacuum degree of 0.03-0.06 MPa for suction filtration, and using a roller to press, and the roller pressure is 0.05-0.1 MPa.
[0055] In some of the above embodiments, vacuum filtration and roller pressing are performed under the above conditions, which can further increase the density of the ceramic fiber board, thereby further improving the heat resistance and strength of the ceramic fiber board.
[0056] In some embodiments, the drying condition is drying at 100-150° C. for 5-12 hours.
[0057] In a second aspect, the present application provides a high temperature resistant ceramic fiberboard, which is prepared according to the method of any embodiment of the first aspect.
[0058] According to the present application, since the high temperature resistant ceramic fiberboard is prepared according to the method of any embodiment of the first aspect, it has the beneficial effects of the first aspect.
[0059] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0060] Zirconia fiber: The raw material is zirconia fiber cotton purchased from Jinan Huolong Thermal Ceramics Co., Ltd., with a product code of HLG-911, a diameter of 3-6 μm, and a length of 30-300 mm. The zirconia fiber cotton is dispersed in water and chopped using a ceramic fiber chopper, and sieved and washed with a filter with a mesh size of 5 mm to obtain zirconia fiber for use.
[0061] Alumina powder was purchased from Zibo Weishuo Fine Ceramic Materials Co., Ltd., model: high temperature low sodium alumina powder, average particle size of 5-200nm, α-alumina content>94%, sodium oxide content<0.1%, iron oxide content<0.2%.
[0062] Silica sol was purchased from Shandong Better New Materials Co., Ltd., model SS3015, particle size 10-15 nm, and silica mass content 30%±1%.
[0063] Graphene oxide was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with a purity of >98.5%, an oxygen content of about 35%, a thickness of 0.6-1.2 nm, and a length of 0.8-2 μm.
[0064] Example 1
[0065] Preparation of high temperature resistant ceramic fiberboard:
[0066] 100 g of zirconia fiber and 350 g of alumina powder were dispersed in 4500 g of water, and after uniform dispersion, 112 g of 30 wt% silica sol binder was added to obtain a mixed solution; then 20 g of acrylamide, 0.5 g of N,N'-methylenebisacrylamide, 2 g of modified graphene oxide, and 1 g of ammonium persulfate were added, and the mixture was reacted at 60°C for 7 h to obtain a slurry.
[0067] The filtration was performed with a vacuum degree of 0.05 MPa, and a roller was used for pressing with a rolling pressure of 0.05 MPa to obtain a wet blank, which was then dried at 115° C. for 8 h to obtain a high-temperature resistant ceramic fiberboard.
[0068] The modified graphene oxide is prepared by the following method:
[0069] Disperse 10 g of graphene oxide in 400 g of ethanol and disperse by ultrasonication. Then add 7 g of vinyltrimethoxysilane and 3 g of (3,3,3-trifluoropropyl)methyldimethoxysilane. Heat to 50 °C and stir to react for 24 h. After the reaction is completed, centrifuge and remove the supernatant. Dry the precipitate at 70 °C for 24 h to obtain modified graphene oxide for use.
[0070] Example 2
[0071] Preparation of high temperature resistant ceramic fiberboard:
[0072] 100 g of zirconia fiber and 350 g of alumina powder were dispersed in 4500 g of water, and after uniform dispersion, 112 g of 30 wt% silica sol binder was added to obtain a mixed solution; then 20 g of acrylamide, 2.5 g of modified graphene oxide, and 1 g of ammonium persulfate were added, and the mixture was reacted at 60° C. for 7 h to obtain a slurry.
[0073] The filtration was performed with a vacuum degree of 0.05 MPa, and a roller was used for pressing with a rolling pressure of 0.05 MPa to obtain a wet blank, which was then dried at 115° C. for 8 h to obtain a high-temperature resistant ceramic fiberboard.
[0074] The modified graphene oxide is prepared by the following method:
[0075] Disperse 10 g of graphene oxide in 400 g of ethanol and disperse by ultrasonication. Then add 7 g of vinyltrimethoxysilane and 3 g of (3,3,3-trifluoropropyl)methyldimethoxysilane. Heat to 50 °C and stir to react for 24 h. After the reaction is completed, centrifuge and remove the supernatant. Dry the precipitate at 70 °C for 24 h to obtain modified graphene oxide for use.
[0076] Example 3
[0077] Preparation of high temperature resistant ceramic fiberboard:
[0078] 100g of zirconia fiber and 350g of alumina powder were dispersed in 4500g of water, and after uniform dispersion, 112g of 30wt% silica sol binder was added to obtain a mixed solution; then 20g of acrylamide, 2.5g of N,N'-methylenebisacrylamide, and 1g of ammonium persulfate were added, and the mixture was reacted at 60°C for 7h to obtain a slurry.
[0079] The filtration was performed with a vacuum degree of 0.05 MPa, and a roller was used for pressing with a rolling pressure of 0.05 MPa to obtain a wet blank, which was then dried at 115° C. for 8 h to obtain a high-temperature resistant ceramic fiberboard.
[0080] Example 4
[0081] Preparation of high temperature resistant ceramic fiberboard:
[0082] 100 g of zirconia fiber and 350 g of alumina powder were dispersed in 4500 g of water, and after uniform dispersion, 112 g of 30 wt% silica sol binder was added to obtain a mixed solution; then 20 g of acrylamide, 0.5 g of N,N'-methylenebisacrylamide, 2 g of modified graphene oxide, and 1 g of ammonium persulfate were added, and the mixture was reacted at 60°C for 7 h to obtain a slurry.
[0083] The filtration was performed with a vacuum degree of 0.05 MPa, and a roller was used for pressing with a rolling pressure of 0.05 MPa to obtain a wet blank, which was then dried at 115° C. for 8 h to obtain a high-temperature resistant ceramic fiberboard.
[0084] The modified graphene oxide is prepared by the following method:
[0085] Disperse 10 g of graphene oxide in 400 g of ethanol and disperse by ultrasonic. Then add 7 g of vinyltrimethoxysilane and heat to 50 °C and stir to react for 24 h. After the reaction is completed, centrifuge and remove the supernatant. Dry the precipitate at 70 °C for 24 h to obtain modified graphene oxide for use.
[0086] Comparative Example 1
[0087] Preparation of high temperature resistant ceramic fiberboard:
[0088] 100g of zirconia fiber and 350g of alumina powder were dispersed in 4500g of water, and after uniform dispersion, 112g of 30wt% silica sol binder was added to obtain a mixed solution; 20g of polyacrylamide was then added to obtain slurry by flocculation and precipitation.
[0089] The filtration was performed with a vacuum degree of 0.05 MPa, and a roller was used for pressing with a rolling pressure of 0.05 MPa to obtain a wet blank, which was then dried at 115° C. for 8 h to obtain a high-temperature resistant ceramic fiberboard.
[0090] The high temperature resistant ceramic fiberboards obtained in Examples 1 to 4 and Comparative Example 1 were tested for their heating permanent linear change rate at 1600°C for 24 hours in the thickness direction according to GB / T 17911-2018, and their flexural strength according to GB / T3001-2017. The results are shown in Table 1.
[0091] Table 1
[0092]
[0093] According to Table 1, the heat resistance and strength of the heat-resistant ceramic fiberboard obtained in each embodiment of the present application are better than those of the comparative example. It should be noted that since the present application mainly solves the influence of the floating of the binder on the ceramic fiberboard during the drying process of the wet blank, it has the greatest influence on the thickness direction of the ceramic fiberboard. At the same time, due to the effect of gravity, the heating permanent line change rate in the thickness direction is generally higher, so its heat resistance is characterized by testing its heating permanent line change in the thickness direction. The heat resistance and strength of comparative example 1 are poor, and the reason may be that the direct use of polyacrylamide and silica sol as a binder cannot effectively inhibit the floating of its binder, resulting in poor bonding effect, thus a large change rate, and low flexural strength. At the same time, there are more surface binders, and the shrinkage rate is greater at high temperatures, so its thickness direction heating permanent line change rate is higher.
[0094] According to Examples 1 to 4, the heat-resistant ceramic fiber board obtained in Example 1 has the best heat resistance and strength, which may be due to the following reasons: in Example 2, only modified graphene oxide is used as a cross-linking agent, which may result in fewer cross-linking sites and lower cross-linking density, so its heat resistance and strength are not as good as in Example 1; in Example 3, only N,N'-methylenebisacrylamide is used as a cross-linking agent. Although it can provide more cross-linking sites, its interaction force with the colloidal particles in the silica sol is small, and the effect of inhibiting the floating of the binder is not as good as in Example 1, so its heat resistance and strength are not as good as in Example 1; in Example 4, only unsaturated bonds are used for grafting in the modified graphene oxide, so its interaction force with the colloidal particles in the silica sol is small, so its heat resistance and strength are not as good as in Example 1, but due to the steric hindrance of the modified graphene oxide, the floating of each binder can also be inhibited to a certain extent, so its heat resistance and strength are better than in Example 2 and Example 3.
[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a high temperature resistant ceramic fiberboard, characterized in that: The following steps are involved: S10: dispersing the refractory ceramic fiber, the refractory ceramic filler and the silica sol binder in water to obtain a mixed solution; S20: adding acrylamide monomers and a cross-linking agent to the mixed solution, initiating polymerization reaction and flocculation to obtain a slurry; Wherein, the cross-linking agent includes N,N'-methylenebisacrylamide and modified graphene oxide, and the modified graphene oxide is obtained by modifying graphene oxide with an unsaturated silane coupling agent and a fluorine-containing silane coupling agent; S30: wet vacuum forming the slurry, and drying it to obtain a high temperature resistant ceramic fiberboard.
2. The method according to claim 1, characterized in that The refractory ceramic fiber includes at least one of polycrystalline mullite fiber, zirconia fiber, and magnesium aluminum spinel fiber; The length of the refractory ceramic fiber is 0.1-10 mm.
3. The method according to claim 1, characterized in that The refractory ceramic filler includes at least one of polycrystalline mullite particles, zirconium oxide particles, and magnesium aluminum spinel particles; The average particle size of the refractory ceramic filler is 5-200 nm.
4. The method according to claim 1, characterized in that: The step S10 specifically includes: 10 parts by mass of refractory ceramic fibers, 15 to 40 parts by mass of refractory ceramic fillers and 5 to 20 parts by mass of a silica sol binder having a solid content of 20 wt % to 40 wt % are dispersed in 300 to 500 parts by mass of water to obtain a mixed solution.
5. The method according to claim 1, characterized in that The acrylamide monomer includes at least one of acrylamide and methacrylic acid amide.
6. The method according to claim 1, characterized in that The modified graphene oxide is prepared by the following method: 10 parts by mass of graphene oxide are dispersed in 200-500 parts by mass of ethanol, and then ultrasonically dispersed. Then, 5-10 parts by mass of vinyltrimethoxysilane and 1-5 parts by mass of (3,3,3,-trifluoropropyl)methyldimethoxysilane are added, and the mixture is heated for reaction to obtain modified graphene oxide.
7. The method according to any one of claims 1 to 6, characterized in that: The mass ratio of the refractory ceramic fiber to the acrylamide monomer is 1:0.1-0.2; the mass ratio of the acrylamide monomer to the cross-linking agent is 1:0.01-0.
2.
8. The method according to claim 7, characterized in that In the step S30, the wet vacuum forming specifically includes: using a vacuum degree of 0.03-0.06 MPa for suction filtration, and using a roller to press, and the roller pressure is 0.05-0.1 MPa.
9. A high temperature resistant ceramic fiberboard, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of light heat-insulating mullite nanofiber aerogel
CN110078425A